Presentation and Outcomes of Kawasaki Disease in Latin American Infants Younger Than 6 Months of Age: A Multinational Multicenter Study of the REKAMLATINA Network - Moreno, Elizabeth; Garcia, S. Diana; Bainto, Emelia; Salgado, Andrea P.; Parish, Austin; Rosellini, Benjamin D.; Ulloa-Gutierrez, Rolando; Garrido-Garcia, Luis M.; Dueñas, Lourdes; Estripeaut, Dora; Luciani, Kathia; Rodríguez-Quiroz, Francisco J.; et al. (Frontiers in Pediatrics, 2020)
Objective: To characterize the clinical presentation and outcomes of Kawasaki disease (KD) in infants < 6 months of age as compared to those ≥ 6 months in Latin America. Methods: We evaluated 36 infants < 6 months old and 940 infants ≥ 6 months old diagnosed with KD in Latin America. We compared differences in laboratory data, clinical presentation, treatment response, and coronary artery outcomes between the two cohorts. Results: The majority (78.1%) of infants and children ≥ 6 months of age were initially diagnosed with KD, as compared to only 38.2% of infants < 6 months. Clinical features of KD were more commonly observed in the older cohort: oral changes (92% vs 75%, P = 0.0023), extremity changes (74.6% vs 57.1%, P = 0.029), and cervical lymphadenopathy (67.6% vs 37.1%, P = 0.0004). Whether treated in the first 10 days of illness or after the 10th day, infants < 6 months were at greater risk of developing a coronary artery aneurysm compared to KD patients ≥ 6 months treated at the same point in the course of illness (≤10 days (53.8% vs 9.4%, P = 0.00012); >10 days (50% vs 7.4%, P = 0.043). Conclusion: Our data show that despite treatment in the first 10 days of illness, infants < 6 months of age in Latin America have a higher risk of developing a coronary artery aneurysm. Delay in the diagnosis leads to larger coronary artery aneurysms disproportionately in these infants. Thus, suspicion for KD should be high in this vulnerable population.